2021
DOI: 10.1021/acs.jafc.1c01949
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Interaction between High Hydrostatic Pressure-Pretreated Rice Bran Protein Hydrolysates and Ferulic Acid: Focus on Antioxidant Activities and Emulsifying Properties

Abstract: Rice bran protein hydrolysates (RBPH) pretreated with high hydrostatic pressure (HHP) covalently interacted with ferulic acid (FA) (0.5 to 2.5 mg/mL) under alkaline conditions. The structural and functional properties of the conjugates were investigated. The results revealed that the FA binding equivalent on RBPH increased from 6.03 to 207.64 nmol/mg. FTIR spectral analysis indicated that the content of α-helix increased, whereas the contents of β-sheet, β-turn, and random coil decreased. The surface hydrophob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…ζ-potential is a key indicator of the emulsion stability. Previous studies had shown that RBPH-FA conjugates can provide higher absolute ζ-potential values versus conventional proteins [ 14 ]. McClements et al [ 32 ] noted that the distribution of some specific bioactive substances on the emulsion interface increased the charge density of droplet surface.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…ζ-potential is a key indicator of the emulsion stability. Previous studies had shown that RBPH-FA conjugates can provide higher absolute ζ-potential values versus conventional proteins [ 14 ]. McClements et al [ 32 ] noted that the distribution of some specific bioactive substances on the emulsion interface increased the charge density of droplet surface.…”
Section: Resultsmentioning
confidence: 99%
“…Elias et al [ 38 ] pointed out that the oxidation of emulsion occurred mainly on the interface. RBPH-FA conjugate as an emulsifier can provide good antioxidant capacity [ 14 ], which can effectively inhibit lipid oxidation on the interface.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations